Circulating DNA in rheumatoid arthritis: pathological changes and association with clinically used serological markers - Elena Rykova; Aleksey Sizikov; Dirk Roggenbuck; Oksana Antonenko; Leonid Bryzgalov; Evgeniy Morozkin; Kseniya Skvortsova; Valentin Vlassov; Pavel Laktionov; Vladimir Kozlov (Arthritis Research & Therapy, 2017)
Abstract Background Early diagnosis of rheumatoid arthritis (RA) is crucial to providing effective therapy and often hampered by unspecific clinical manifestations. Elevated levels of extracellular circulating DNA (cirDNA) in patients with autoimmune disease were found to be associated with etiopathogenesis. To our knowledge, this is the first study to investigate the putative diagnostic use of cirDNA in RA and its association with disease activity. Methods Blood samples were taken from 63 healthy subjects (HS) and 74 patients with RA. cirDNA was extracted from plasma and cell surface-bound cirDNA fractions (csbDNA). cirDNA concentration was measured by quantitative real-time polymerase chain reaction. Rheumatoid factor was analyzed by immunonephelometry, whereas C-reactive protein and anticitrullinated protein/peptide antibodies (ACPA) were detected by enzyme-linked immunosorbent assay. Results Plasma cirDNA was significantly elevated in patients with RA compared with HS (12.0 versus 8.4 ng/ml, p < 0.01). In contrast, nuclear csbDNA (n-csbDNA) was significantly decreased (24.0 versus 50.8 ng/ml, p < 0.01), whereas mitochondrial csbDNA (m-csbDNA) was elevated (1.44 × 106 copies/ml versus 0.58 × 106 copies/ml, p < 0.05) in RA. The combination of csbDNA (mitochondrial + nuclear) with ACPA reveals the best positive/negative likelihood ratios (LRs) for the discrimination RA from HS (LR+ 61.00, LR− 0.03) in contrast to ACPA (LR+ 9.00, LR− 0.19) or csbDNA (LR+ 8.00, LR− 0.18) alone. Conclusions Nuclear and mitochondrial cirDNA levels in plasma and on the surface of blood cells are modulated in RA. Combination of cirDNA values with ACPA can improve the serological diagnosis of RA.